Patients with true mixed growth hormone and prolactin-secreting pituitary adenoma: a case series of 12 patients. (3rd March 2020) - Gulbadin, Daqiq; Li, Zhiwei; Shahbaz, Muhammad; Farhaj, Zeeshan; Shabbir, Arzoo; Qi, Qichao; Tang, Kuanxiao; Ni, Shilei; Sun, Lei
Abstract: Objective: Mixed growth hormone (GH) and prolactin (PRL) secreting adenomas are the most common type of plurihormonal pituitary adenomas. We assessed the clinical presentations and impacts of transsphenoidal surgery (TS) on patients with mixed GH and PRL adenomas including surgical outcomes, complications, and prognosis. Method and patients: Twelve patients (7 males, 5 females) were operated in the neurosurgery department of Qilu hospital affiliated to Shandong University, Shandong, China. We analyzed hormone levels of preoperation, postoperation (within 24 h) and at 12-month follow-up and correlated levels with tumor volumes. Results: The remission rate was 66.7% (8/12), the recurrence rate was 16.7% (2/12), the cause-specific mortality was 0 and the overall mortality rate was 16.7% (2/12) due to stroke and myocardial infarction respectively. A significant drop was seen in GH, PRL, and Insulin-like-growth-factor-1 (IGF-1) levels between preoperation and postoperation with mean values from 52.6 to 9.9 ng/ml ( p  = 0.0015), from 321.6 to 190.9 ng/ml ( p  = 0.0026) and from 815.7 to 230.6 ng/ml ( p  = 0.0004), respectively. This drop was more significant between preoperation and follow-up with mean values from 52.6 to 3.0 ng/ml ( p  = 0.002), from 321.6 to 61.6 ng/ml ( p  < 0.0001), and from 815.7 to 195.0 ng/ml ( p  = 0.0001), respectively. However, there was no significant correlation between tumor volume and all of the hormone levels. Conclusions: Most mixed GH and PRL adenomas are aggressive with a high risk of recurrence and mortality.